Price dynamics and trader overconfidence - Steffen Ahrens; Ciril Bosch-Rosa; Rasmus Roulund (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Overconfidence is one of the most important biases in financial markets and commonly associated with excessive trading and asset market bubbles. So far, most of the finance literature takes overconfidence as a given, "static" personality trait. In this paper we introduce a novel experimental design which allows us to track different measures of overconfidence during an asset market bubble. The results show that overconfidence co-moves with asset prices and points towards a feedback loop in which overconfidence adds fuel to the flame of existing bubbles.
Keywords: C91; D84; G11; G41; 330; overconfidence; experiment; asset markets